Gender differences in Syrian refugees in Jordan: Psychological, self-esteem, family function, marital satisfaction, and life satisfaction. (May 2023) - Al-Krenawi, Alean; Bell, Melissa M
Aim: The current study examined gender differences in mental health, self-esteem, family function, marital satisfaction, and life satisfaction between men and women living in a refugee camp for Syrian refugees in Jordan. Method: A snowball method used by local female and male students trained to collect data according to culturally competent methods. The following research instruments were deployed: Symptoms Checklist-SCL90, Self-esteem Scale, the McMaster Family Assessment Device, Marital Satisfaction Scale, and life Satisfaction Scale. Results: A sample of 290 adults (196 women and 94 men) living in a refugee camp in Jordan participated in the study. Findings revealed that marital satisfaction, self-esteem, and life satisfaction were significantly different between males and females, indicating less subjective well-being for women. Many of the mental health symptoms in this study were more common for women than men; particularly noteworthy were somatization, obsessive compulsive behavior, interpersonal sensitivity, depression, hostility, psychoticism, and higher scores on the Global Severity Index (GSI). Conclusion: While some stressors are not gender-specific, there are unique factors that women face which place them at increased risk of mental health problems. Implications for practice include a greater understanding of the challenges and resilience mechanisms that are related to gender and culture.